INDONESIAN PROPERTY AND REAL ESTATE RETURN ANALYSIS : COMPARISON OF CAPITAL ASSET PRICING MODEL AND FAMA-FRENCH THREE FACTORS MODEL - M. Bobby Afif Nasution; Hermanto Siregar; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2020)
A nation’s economic growth can be reflected in property and real estate sector growth. Property and real estate are believed to be one leading sector that is indicating a nation economic health, as this sector grows alongside the national economic growth. Property and real estate are a long term business that requires a large sum of capital. Therefore, many firms in these sectors listed their share in the capital market to attract potential investment form investors. However, property and real estate have risks due to its long term nature, which the investors must avoid. This research aimed (1) to determine two major risks on the property and real estate, economic growth and firms size, and value stocks by using Capital Asset Pricing Model and Fama-French Three Factor Model; (2) and to identify the best model that could detect the best return for property and real estate sector. The result showed that the economic condition was significantly affecting the Indonesia property and real estate sector’s excess return. Large size with low book-to-market ratio firms were dominating the property and real estate sector. In conclusion, both models showed similar and consistent results; however the Fama-French Three-Factor Model was better in identifying excess return of Indonesian property and real estate sectors. Keywords: CAPM, property and real estate, three factor model Abstrak: Pertumbuhan ekonomi negara dapat tercermin dari bagaimana sektor properti dan real estate tumbuh. Properti dan real estate diyakini sebagai salah satu sektor terkemuka yang menunjukkan kesehatan ekonomi di suatu negara, karena sektor-sektor tersebut tumbuh seiring dengan pertumbuhan ekonomi. Properti dan real estate cenderung bersifat jangka panjang dan membutuhkan modal besar. Oleh karena itu, banyak perusahaan di sektor ini mendaftarkan saham mereka di pasar modal, untuk menciptakan potensi investasi yang baik bagi investor. Namun, karena sifatnya yang jangka panjang, properti dan real estate memiliki risiko di mana investor harus menghindarinya. Penelitian ini bertujuan untuk menentukan dua risiko utama pada properti dan real estate, pertumbuhan ekonomi dan ukuran serta nilai saham perusahaan dengan menggunakan model CAPM dan Fama-French, dan membandingkan model mana yang dapat mengidentifikasi pengembalian yang lebih baik untuk sektor properti dan real estate. Penelitian menunjukkan bahwa kondisi ekonomi secara signifikan mempengaruhi kelebihan return properti dan real estat Indonesia. Perusahaan dengan ukuran perusahaan besar dan rasio book-to-market yang rendah diketahui mendominasi sektor properti dan real estate. Secara keseluruhan, kedua model menunjukkan hasil yang sama dan konsisten, namun Fama-French Three Factor Model dipastikan lebih baik dalam mengidentifikasi kelebihan pengembalian sektor properti dan real estat Indonesia. Kata kunci: CAPM, property and real estate, three factor model